Quality of Service Analysis on EaTrain Application at A Restaurant on A Train - Destanuari Sufia Mukti; Nurul Hidayati; Abdul Rasyid (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2023)
One of the services on the train is a dining car that sells food and drinks. However, the current system has problems such as the unclear position and operating hours of the dining car, the lack of menu information, and the difficulty of officers in giving change. The purpose of this research is to make it easier for passengers to order food and drinks, increase the officer’s efficiency in managing menu, and determine the network quality while using the EaTrain application on the train. The EaTrain application was built using android studio with cloud firestore as a database for storing data, and integrated with midtrans payment gateway in making payments. Wireshark software is used to measure the network quality of EaTrain application in train restaurant. The test results show that the EaTrain application can run well on Android 7.0 devices and above. The value of delay, throughput, and packet loss in Quality of Service (QoS) testing while making payments is determined by network quality of each provider. Provider A has average delay of 123ms, packet loss is 10.72%, and throughput is 3974 bps. While provider B has average delay at 1343ms, packet loss is 50.88%, and throughput is 33628 bps.